2001
DOI: 10.1111/j.1600-051x.2001.281209.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of the effectiveness of novel sonic instruments and curettes for periodontal debridement after 2 months

Abstract: Clinical comparison of the effectiveness of novel sonic instruments and curettes for periodontal debridement after 2 months.Abstract Aim: The aim of this study was to evaluate in vivo the effectiveness of scaling and root planing of new oscillating instruments (Periosonic A ) using a sonic handpiece compared to hand curettes with a split mouth design after 2 months. Methods: 11 patients with adult periodontitis participated in this study. Plaque index (PII) (O'Leary), bleeding on probing (BOP), probing pocket … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
3
10
0
Order By: Relevance
“…Both treatment methods were similarly effective in PPD reduction and CAL gain. These results are in accordance with data reported in different recent meta-analyses (Tunkel et al 2002 Beuchat et al (2001) showed a greater PPD reduction in deep periodontal pockets with another sonic scaler (Periosonic: 2.4 mm versus S/RP: 3.0 mm). Loos et al (1989) found a PPD reduction of 2.3 mm in their study.…”
Section: Negative Side Effectssupporting
confidence: 93%
“…Both treatment methods were similarly effective in PPD reduction and CAL gain. These results are in accordance with data reported in different recent meta-analyses (Tunkel et al 2002 Beuchat et al (2001) showed a greater PPD reduction in deep periodontal pockets with another sonic scaler (Periosonic: 2.4 mm versus S/RP: 3.0 mm). Loos et al (1989) found a PPD reduction of 2.3 mm in their study.…”
Section: Negative Side Effectssupporting
confidence: 93%
“…Characteristics of articles selected for secondary outcomes appear in Table 2. Reasons for study exclusion appear in Table 3 [5,6,10,.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…For example, Beuchat found that when initial PPD < 6 mm, for gingival recession (GR), there was no statistical difference between ultrasonic and manual subgingival scaling (P < 0.05). When initial PPD > 7 mm, attachment level (AL) improved more while GR reduced more in using ultrasonic instruments than using manual instruments [10]. It is controversial in terms of when to use manual subgingival instruments and when to use ultrasonic ones.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic debridement (UD) has been extensively reported in the literature and is a primary procedure in the provision of professional oral prophylaxis 5,14) . Professional oral prophylaxis should be as nonaggressive as possible, however, so there are a number of procedures available to suit the oral health of the individual concerned 2) .…”
Section: Introductionmentioning
confidence: 99%